PENGARUH PENGGUNAAN TEKHNIK KEPALA BERNOMOR DALAM KEMAMPUAN SISWA DALAM MEMAHAMI TEKS NARATIVE KELAS 2 SMA NEGERI 5 DUMAI DALAM TEKS NARATIVE - ', Suhaila; Azhar, Fadly; Aruan, Rumiri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research was designed to investigate whether there is a significant effect of Numbered Head Together technique on the students’ ability in comprehending narrative text. This research took place at SMA NEGERI 5 Dumai from April to May 2017. The sample was 42 students from XI-1 and XI-2 Social major that took by using cluster random sampling technique. The test containingg 35 items was used to collect the data. The technique of data analysis was paired sample t-test. The research findings found that there was a significant difference of students’ reading comprehension on narrative text after being taught through Numbered-Head-Together technique. Based on the data analysis, it was found that t-test (6.037)was bigger than t-table (2.086). This suggested that Numbered-Head-Together technique was effective in teaching reading narrative text.Keywords: Numbered Head Together, Reading Comprehension, Narrative Text